PENGARUH USIA DAN LAMA KERJA BIDAN TERHADAP KESADARAN SOSIAL BIDAN DALAM PEMBERIAN TABLET FE PADA IBU HAMIL - Agus Aan Adriansyah (Fakultas Kesehatan Masyarakat, Universitas Jember, 2017)
Coverage of Fe tablets during antenatal care visit from 2011-2013 in Public Health Centers in Surabaya was still low with an average percentage of 9.29% and 16.27%. The study aim to analyze effect of midwife’s age and length of employment towards social awareness of midwife in Fe tablets administration for pregnant women in Public Health Centers in Surabaya.This research was an analytic observational study and a cross sectional approach. The research location was in all Public Health Centers in Surabaya. The samples as many as 65 midwives were taken using multistage random cluster sampling technique from 62 Public Health Centers representing every region in Surabaya. The data obtained were analyzed by using Ordinal Logistic Regression technique.The results showed that the older midwives (more than 36 years) have a better social awareness since they have had experience in interacting with the social world. Midwives who work longer (more than 10 years) tend to have better social awareness.The conclusion of this study is that the midwife’s age and length of employment are closely towards social awareness of midwife. Keyword: Social Awareness, Midwife, Fe tablets